Comparison of the suitability of intra-oral scanning with conventional impression of edentulous maxilla in vivo. A preliminary study - D’Arienzo, Luigi Federico; D€™Arienzo, A.; Borracchini, A. (Journal of Osseointegration, 2018)
Aim According to recent literature, the accuracy of digital impression can be compared with traditional impressions for most indications. However, little is known about their suitability in digitizing edentulous jaws in view of mobile prosthetic rehabilitation. The aim of this study was to compare in vivo an intra-oral scanner with conventional impression in case of maxillary edentulous jaws. Material and methods Four (1 male, 3 female) subjects who had no previous experience with either conventional or digital impression participated in this study. Digital impression were taken using an intra-oral scanner. After that conventional impressions of maxillary edentulous jaws were taken with an irreversible hydrocolloid impression material. Then all IOSs datasets were loaded in a three-dimensional evaluation software (3DReshaper 2017, Hexagon), where they were superimposed on the model obtained using conventional impression and compared. Results The mean value of difference between the two impression techniques ranged from 219 to 347 Î¼m. The comparison of models obtained with the two techniques showed that the compression given by the impression material on the peripheral areas, such as oral vestibule and soft palate, determined the most important differences recorded. Conclusion Digitizing edentulous jaws with the use of IOS appeared to be feasible in vivo, although peripheral tissue were not effectively reproduced. On the basis of the results of this study, the authors could not recommend the use of IOS for digitization of edentulous jaws in vivo in view of mobile prosthetic rehabilitation, until it will be found a way to give a selective pressure in peripheral areas as occurs during edging of impression tray.